Многоэлементные детекторы ионизирующего излучения - Синьков М. В. Михаил Викторович; Сапрыкин В. Д. Василий Данилович; Чалая В. Г. Валентина Григорьевна; Терновой С. К. Сергей Константинович; Зозуля Ю. И. Юрий Иванович (Киев, Технiка, 1985)
Авт. указаны на обороте тит. л.